使用 SQ4R 学习法提高丹戎布拉大学师范教育学院汉语专业 2019 届学 生的阅读理解能力 - Shi Oi; Lily Thamrin; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractReading comprehension ability is an ability that is mastered through the sense of vision to read letters and understand the contents of text. Because student’s attitudes toward reading are still passive, students during reading lessons are not focused make their reading comprehension ability is lacking. Therefore, author motivated to conduct research using learning model SQ4R to improve students reading comprehension ability. This research uses experimental research methods, true experimental design with one group pretest-posttest design. This research sample were students of generation 2019 mandarin language education study program at FKIP Untan, there were 33 students. The data collection methods were observation, written tests (pretest and posttest), and student’s response questionnaires. This research results were analyzed using SPSS 2.0 program. This research results were average results of the learning process using learning model SQ4R was 74,22%, indicating that the learning process belongs to the good category; T-test pretest and posttest results of experimental group was the value sig 0,000>α (0,05), Ha accepted, showing that there was significant improvement in learning outcomes from pretest and posttest. The questionnaires results showed the average percentage of student responses to the learning model SQ4R was 72,84%, indicating that students reponses was good.Keywords: Improve, Reading Comprehension Ability, Learning Model SQ4R